2018
DOI: 10.31393/bba30-2018-06
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic model parameters of kidney in men and women endo-mesomorphic somatotype depending on the anthropometric indices characteristics

Abstract: The application of the mathematical method for establishing quantitative relationshipsbetween the set of anthropometric parameters and sonographic parameters of thepatient allows in some cases to significantly improve early diagnosis of diseases, makeit not only timely, but accurate. The purpose of the work is to analyze the regressionmodels of individual sonographic sizes of the kidneys in practically healthy men andwomen of the endo-mesomorphic somatotype, depending on the peculiarities of thestructure and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In previous studies [4,31], we found that in practically healthy women of mesomorphic somatotypes of 16 possible sonographic parameters of the right and left kidneys, based on anthropometric and somatotypological indicators, were constructed 7 reliable models with a determination coefficient from 0.607 to 0.641, and for women endo-mesomorphic somatotype -14 valid models with a determination coefficient from 0.672 to 0.912. In women of mesomorphic somatotype constructed models most often include the circumferential dimensions of the body (29.8%) and cephalometric indices (19.1%).…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies [4,31], we found that in practically healthy women of mesomorphic somatotypes of 16 possible sonographic parameters of the right and left kidneys, based on anthropometric and somatotypological indicators, were constructed 7 reliable models with a determination coefficient from 0.607 to 0.641, and for women endo-mesomorphic somatotype -14 valid models with a determination coefficient from 0.672 to 0.912. In women of mesomorphic somatotype constructed models most often include the circumferential dimensions of the body (29.8%) and cephalometric indices (19.1%).…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies [4,27,28] we determined that from 16 possible sonographic parameters of the kidneys, based on the anthropometric and somatotypological indices in practically healthy women of the mesomorphic somatotype, 7 reliable models with a determination coefficient from 0.607 to 0.641 were constructed; in women of ectomorphic somatotype -all 16 models with a determination coefficient from 0.607 to 0.973; in women endo-mesomorphic somatotype -14 models with a determination coefficient from 0.672 to 0.912. The most frequently constructed models included: women with mesomorphic somatotypecircumferential body dimensions (29.8%) and cephalometric indexes (19.1%); in women with ectomorphic somatotype body diameters (24.2%), body girth sizes (20.9%), cephalometric indices (19.8%) and thickness of skin and fat folds (14.3%); in women of the endo-mesomorphic somatotype, the cephalometric indexes (to the right kidney 24.2%, to the left kidney 15.6%), body diameters (to the right kidney 24.2%, to the left kidney 17.8%) and the circumferential body size (to the right kidney 24.2%, to left kidney 22.2%), and also only to the left kidney thickness of skin and fat folds (17.8%).…”
Section: Discussionmentioning
confidence: 94%
“…However, somatotype could also be an important measurement parameter for the risk of CKD. To the best of our knowledge, although only one study has analysed the sonographic model parameters of patients with endomesoporic kidneys for anthropometric index characteristics, no studies were found that directly assessed the somatotype characteristics of patients with CKD (Ustymenko, 2018).…”
Section: Introductionmentioning
confidence: 99%